GHANAIAN CONSTRUCTION PROFESSIONALS’ PERCEPTION ON CHALLENGES TO FEMALE RETENTION IN THE CONSTRUCTION INDUSTRY - J Ayarkwa; K Agyekum; A Acheampong (Journal of Construction Project Management and Innovation)
The flow of knowledge from higher learning institutions into the construction industry is always disrupted when female graduates are not retained in the Ghanaian construction industry. This paper assesses challenges to female graduates’ retention in the Ghanaian construction industry, and recommends measures to promote their retention and participation in infrastructure development. Questionnaires were administered through purposive sampling to 51 groups of male and female construction professionals in order to establish the gender differentiated perceptions on the challenges and measures to retain female construction graduates within the construction industry. Professionals from construction companies and consultancy firms were surveyed using self-administered questionnaires. Data was encoded into SPSS and analysed using both one sample t-test and Wilcoxon–Mann-Whitney two-sample rank-sum test. The survey instrument assessed the views of respondents on issues relating to the under-representation of women in the construction industry, challenges to their retention and measures to retain them in the construction industry. Professional men and women in the construction industry see better prospects in other industries, family commitments, long working hours and stressful work environment as some of the factors which push women away from the industry. Professional associations and regulatory bodies should use strategies such as mentoring, increase in role models, eliminating gender bias factors, giving career guidance, and increasing construction higher education to attract and retain professional women in the industry. The strategies suggested in this paper will help attract and retain female graduates in the Ghanaian construction industry to enable them effectively participate in infrastructure development. The barriers to female retention, the strong push factors identified and the measures suggested for female retention are of value to construction practitioners and learning institutions in Ghana and other African countries